AGRESIVITAS PAJAK BERDASARKAN UKURAN PERUSAHAAN, PENDANAAN ASET DAN KOMPOSISI ASET SERTA PROFITABILITAS (STUDI SEKTOR MANUFAKTUR DI NEGARA BERKEMBANG) - Shahnas Regina Fajar; Patricia Diana (Universitas Multimedia Nusantara, 2020)
The purpose of this research is to investigate the association between firm size using Ln total asset, asset funding using Debt to Total Asset (DAR) and asset composition, and also profitability using Return on Asset (ROA) on tax aggressiveness using Effective Tax Rate (ETR). Sample in this research were manufacturing public company which listed consecutively during period 2016-2018. The others criteria were publishing audited financial statement, using Rupiah as reporting currency, have same reporting period which ended at December 31, positively profit and also have assets value within 1 up to 4 trillion. Data analysis method used multiple regression. The result of this research found that only asset funding (DAR) has significant positive effect towards tax aggressiveness (ETR) while firm size, profitability (ROA) and asset composition (CAIR) has no effect on tax aggressiveness (ETR. Keywords: Capital Intensity, Firm Size, Leverage, Profitability, Tax Aggressiveness.